PENGARUH PEMBERIAN KULIT BUAH NAGA TERFERMENTASI DENGAN Saccharomyces cerevisiae DALAM RANSUM TERHADAP KARKAS AYAM KAMPUNG UMUR 10 MINGGU - I M. J., Antara; Dewi, G. A. M. K.; Wiyana, I K. A. (Jurnal Peternakan Tropika; Vol 5 No 2 (2017), 2017)
This study aim to determine the effect of dragon fruit with Saccharomyces cereviseae on diets to chicken carcass age of 10 weeks. This research has been conducted in the Faculty of Animal Husbandry Research Station, Jimbaran, Badung Regency for 100 weeks. Chickens used were 100 head of local chicken (Gallus domesticus). The design use was Completely randomized design with four treatments and five replications.The control diet is chicken were offered diets without dragon fruit (RKBN 0 ), diets with skin dragon fruit fermented Saccharomycescerevisiae 5% (RKBN 1 ), diets with skin dragon fruit fermented Saccharomycescerevisiae 7% (RKBN 2 ), and diets with skin dragon fruit fermented Saccharomycescerevisiae 9% (RKBN 3 ). Drinking water and feed were offered ad libitum. The variables measured were: slaughter weight, carcass weight, and carcass percentage and parts of carcass. The results showed that administration of dragon fruit peel fermented with Saccharomyces cerevisiae 7% (RKBN 2 ) and 9% (RKBN 3 ) differ significantly (P<0.05) compared with that obtained ration chicken without skin dragon fruit fermented with Saccharomyces cerevisiae (RKBN 0 ) in the variable slaughter weight, carcass weight, breast weight, and the weight of the wing just carcass percentage, weight back and thigh weights had no significant (P>0.05). Based on research can be concluded that the administration of skin dragon fruit fermented Saccharomyces cerevisiae as much as 9% (RKBN 3 ) on chicken can increase slaughter weight, carcass weight, and part of carcass (breast and wing) and the provision of as much as 7% (RKBN 2 ) can increase the weight beef, carcass weight and carcass recahan on the wings while giving as much as 5% (RKBN 1 ) does not affect the slaughter weight, carcass weight, carcass percentage and parts carcass on (weight breast, wings, back and thighs).
Keywords: Local chicken, skin of dragon fruit, part of carcass, Saccharomyces cerevisiae